STUDI ISLAM DALAM PENDEKATAN HISTORIS: (Studi Atas Tawaran Pemikiran Ibrahim M. Abu Rabi') - Minhaji Minhaji; Luluk Maktumah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
View of the west against the Islamic world to be changed. Islamic doctrine justified as violence, intolerance, terrorism, and the threat to Western society and the world global terms. It happened after the WTC bombing March 11, 2001. The meaning of Islam shifted from teaching about the principles of peace become violent theology, Islam is seen as monolithic, partial, incomplete. It was also made clear by "Islamophobia" as a sign of change in the West's image on Islam. those disturb the Muslim life. The Western assessment is actually very easy to argue for two reasons; Islam never teaches violence, and Islam as a universal religion, but it is, then, impressed very apologists and it's not an option to get out of the unfavorable conditions. The problem had been studied by Ibrahim M Abud Rabi ' through "historical-empirical". His studies focus was not on theology of violence, but he had just a frame of mind to criticize premises starting from the history of modern development, Islamic educational system, the development of Islamic studies, related with the socio-religious life in Arab-Islamic countries. Islamic responses to Western progress, and followed with the responses of the elite to all.